The Evaluation of Hepatocyte Function After ESWL with Hepatobiliary Scintigraphy - M. Refik MAS; Ayhan DİNÇ and A. Kemal GÜRBÜZ and Ümit ATEŞKAN and Cem GÖNLÜŞEN and Tahir ÜNAL and Selahattin ERİKÇİ and Kenan SAĞLAM and Emel ÖZTÜRK and Fikri KOCABALKAN (Turkish Journal of Gastroenterology, 2020)
-